Laboratory Analysis of Soil Physicochemical Properties Based on Agricultural Fertilizer Input Requirement Application: A Case of Haramaya University, Ethiopia - Turyasingura, Benson; Chavula, Petros; Mohammed, Yasin; Eliyas, Abdi Alic; Girmac , Tesfasilassie; Sadeso, Kumale; Shentema, Solomon; Abebed, Aschalew; Katel, Shambhu; Timsina, Sandipa (Plant Physiology and Soil Chemistry (PPSC), 2023)
This study aimed at assessing the soil with detail information about soil properties that are basic for agricultural input requirements such as fertilizer application. It was guided by the specific objectives which include identifying the different steps taken to undertake soil physical, chemical properties and providing basic data on the physical and chemical properties of the selected soil sampling site at Haramaya University, Ethiopia. The laboratory analysis aimed at finding out the physical and chemical soil properties on the deliberate selected area indicated sand-loamy, clayey and sand. The profiles shows some variations in the patterns of the horizons within a profile. Among the soil chemical characteristics, it was found that the soil pH in soil-water suspension varied from 7.63-7.65. Electro-conductivity was very low varying from 0.08 to 1.00 ds/m with an average value of 0.54 ds/m. The maximum exchangeable sodium percentage (ESP) value calculated is 6.36 % where the minimum is 0.36 % and averaged value of 3.36 %. Cation Exchange Capacity ranged from 13.20 to 40.38cmol (+)/kg of soil, with mean value of 27.94 cmol (+)/kg. Exchangeable calcium ranged 4.99 cmol (+)/kg to 18.34 cmol (+)/kg with a mean of 12.02 cmol (+)/kg which is rated as high. The potassium value of (0.05, 0.82 meq/100gm), 0.06 meq/100gm and (0.13, 0.46 meq/100gm) of soil respectively. The value of the measured exchangeable sodium ranged from 0.12 to 1.22 meq/100g of soil, with a mean value of 0.44 meq/100g of soil indicating medium sodium content of the soil. Total nitrogen ranging from 0.11 to 0.37 percent which decreases from top to sub soil. In conclusion soil and agronomic management are correlated with the well being of soil. Therefore, it is recommended that integrated nutrient management activities should be adopted in the study area for optimum and sustainable production of major crops.